LUMENAL PLASMA MEMBRANE OF THE URINARY BLADDER : I. Three-Dimensional Reconstruction from Freeze-Etch Images - Staehelin, L. Andrew (The Rockefeller University Press, 1972)
To determine the three-dimensional structure of the lumenal membrane of transitional epithelium, a study was made of sectioned, negatively stained, and freeze-etched specimens from intact epithelium and membrane fractions from rabbit urinary bladder. Particulate membrane components are confined to plaque regions within which the unit membrane is asymmetric, having a thicker outer leaflet. Transversely fractured freeze-etched plaques display a thick (∼80 A), particulate lumenal leaflet and a thin (∼40 A) cytoplasmic one. Four different faces of the two leaflets can be distinguished: two complementary, split, inner membrane faces exposed by freeze-cleaving the bilayer and two external (lumenal and cytoplasmic) membrane surfaces revealed by deep-etching. On the split, inner face of the lumenal leaflet appear polygonal plaques of hexagonally arranged particles. These fit into holes observed on the complementary, split, innerface of the cytoplasmic leaflet. The particles, which have a center-to-center spacing of ∼160 A, also seem to protrude from the external surface of the lumenal leaflet, where their subunits (∼50 A in diameter) are revealed by freeze-etching and negative staining. The plaques are separated from each other by smooth-surfaced regions, which cleave like simple lipid bilayers. Since the array of plaque particles covers only ∼73% of the membrane surface area, whereas 27% is taken up by particle-free interplaque regions, the presence of particles cannot in itself entirely account for the permeability barrier of the lumenal membrane. Although no particles are observed protruding from the cytoplasmic surface of the membrane, cytoplasmic filaments are attached to it by short, cross-bridge-like filaments that seem to contact the particles within the membrane. These long cytoplasmic filaments cross-link adjacent plaques. Therefore, we suggest that at least one function of the particles is to serve as anchoring sites for cytoplasmic filaments, which limit the expansion of the lumenal membrane during distention of the bladder, thereby preventing it from rupturing. The particle-free interplaque regions probably function as hinge areas between the stiff plaques, allowing the membrane to fold up when the bladder is contracted.